Dialogue Spaces for the Transition to the Social Model of Care for People With Disabilities: A Look From the Participatory Action Research - Córdoba-Warner, Eugenia (Revista Electrónica Educare, 2020)
This article aims to expose the need for an evolution of the rehabilitation model to the social model of care for people with disabilities in special education centers. Through the participatory action research (PAR) approach, the dynamics of a professional team of the multiple disability early stimulation service at a special education center was studied; this center has a special education teacher, a language therapist, and two physical therapists. The research was conducted through the systematization of experiences of six meetings held by the interdisciplinary team, constituted as a learning community. The participants discovered that they had different visions about the same fact. They also found that thinking that they were acting under a social model, they continued to work, in many occasions, under the rehabilitation model, as demonstrated by their position towards students and, especially, to families. It is concluded that dialogue spaces must be opened where interdisciplinary teams can be a source of change in the understanding of educational processes and the complexity of relationships with children and their families; these spaces can be opened from a perspective based on human rights, as it is the social model of care for people with disabilities.